Frequency and association of polymorphisms in CSN3 gene with milk yield and composition in Saanen goats - Catota-Gómez, Luis David; Parra-Bracamonte, Gaspar Manuel; Cienfuegos-Rivas, Eugenia Guadalupe; Hernández-Meléndez, Javier; Sifuentes-Rincón, Ana María; Martínez-González, Juan Carlos (Ecosistemas y Recursos Agropecuarios, 2017)
K-casein (CSN3) gene is of particular interest in goat production due to the e ect of its polymorphisms on milk quality and composition. The objective of this study was to assess the genotypic and allelic frequencies in CSN3 gene in the Saanen goat breed and its e ect on milk production and some of its compositional traits. Allelic discrimination assays were designed to determine the variants (A, B or C) using qPCR and allelic discrimination method. Allelic frequencies for A, B and C were 0.23, 0.64 and 0.13, respectively. Association analysis indicated that the CSN3 was signi cantly associated only with protein percentage (p = 0.006). Results indicated that animals with AC, BB and CC genotypes showed higher milk
Keywords: Goat; Kappa casein; Milk; Protein.